Kajian Eksistensi terhadap Bahasa Indonesia sebagai Bahasa Persatuan dan Bahasa Negara di Era Globalisasi - Delila Maya Sari Siregar; Eshaulin Br Sembiring; Lora Ernanta Tarigan; Yosua Gabe Maruli Sijabat (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
Language is a need for everyone. Language is also an element of culture and a symbol for a person to communicate all needs. For the Indonesian people, Indonesian has a very important position because Indonesian is the national language and state language. Indonesian as the national language as a nation was built on the basis of ethnic and cultural diversity, Indonesia has good capital in fostering a sense of nationalism and strengthening national identity through the use of Indonesian. The existence of the Indonesian language, which is the identity of the Indonesian nation in the current era of globalization, needs to be fostered and socialized by every Indonesian citizen. This is necessary so that the Indonesian people are not carried away by foreign influences and culture that are not in accordance with the language and culture of the Indonesian people. The influence of such sophisticated communication tools must be faced by maintaining the identity of the Indonesian nation, including the identity of the Indonesian language. This all concerns the discipline of speaking the national language, by complying with all the rules or regulations for using the Indonesian language. Globalization affects all aspects of life, including language. The increasingly global language used by all nations in the world is English, which has more than one billion users.